2023
DOI: 10.2169/internalmedicine.0744-22
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Persistent Atrial Fibrillation Concomitant with Pectus Excavatum

Abstract: A 19-year-old man with pectus excavatum developed symptomatic persistent atrial fibrillation (AF). He had no remarkable medical history or comorbidities and had not exercised intensely during childhood. Electrical cardioversion and pre-treatment with amiodarone for two months failed to maintain sinus rhythm. Computed tomography before ablation revealed compression of the right and left atria between the sternal bone and vertebral bodies. Voltage mapping revealed that the right and left atrial voltages were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…RFCA for AF, especially PVI, is an effective and well‐established procedure for maintaining sinus rhythm. Although the efficacy of RFCA for AF in patients with PE has not been demonstrated in a large clinical trial, several individual case reports have reported the same 5 . This is the first three‐patient case series showing efficacy and the various challenges imposed by PE during the ablation procedure.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…RFCA for AF, especially PVI, is an effective and well‐established procedure for maintaining sinus rhythm. Although the efficacy of RFCA for AF in patients with PE has not been demonstrated in a large clinical trial, several individual case reports have reported the same 5 . This is the first three‐patient case series showing efficacy and the various challenges imposed by PE during the ablation procedure.…”
Section: Discussionmentioning
confidence: 82%
“…This case series explains the importance of understanding abnormal cardiac anatomy and strategizing before ablation procedures in patients with structural defects like PE. 5 The presence of PE can cause rotation and displacement of the heart, imposing challenges during RFCA of AF. The challenges include difficult access to the CS due to sharp angulation, ablation of the CTI due to anatomic distortion, and challenges of PVI due to reduced anteroposterior diameter, minimizing freedom of catheter movement.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations